2011
DOI: 10.1105/tpc.111.088112
|View full text |Cite
|
Sign up to set email alerts
|

Two Mechanosensitive Channel Homologs Influence Division Ring Placement in Arabidopsis Chloroplasts

Abstract: Chloroplasts must divide repeatedly to maintain their population during plant growth and development. A number of proteins required for chloroplast division have been identified, and the functional relationships between them are beginning to be elucidated. In both chloroplasts and bacteria, the future site of division is specified by placement of the Filamentous temperature sensitive Z (FtsZ) ring, and the Min system serves to restrict FtsZ ring formation to mid-chloroplast or mid-cell. How the Min system is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
81
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 86 publications
(91 citation statements)
references
References 89 publications
10
81
0
Order By: Relevance
“…Reverse genetic analyses have demonstrated that two plastid-localized homologs, MSL2 and MSL3, are required for the proper size, shape, division, and hypoosmotic volume control of plastids (14)(15)(16). In addition, two plasma membranelocalized homologs, MSL9 and MSL10, are genetically required for the predominant MS channel activity in the plasma membrane of Arabidopsis root cell protoplasts, providing support for the hypothesis that MSL proteins form MS channels (5).…”
mentioning
confidence: 90%
“…Reverse genetic analyses have demonstrated that two plastid-localized homologs, MSL2 and MSL3, are required for the proper size, shape, division, and hypoosmotic volume control of plastids (14)(15)(16). In addition, two plasma membranelocalized homologs, MSL9 and MSL10, are genetically required for the predominant MS channel activity in the plasma membrane of Arabidopsis root cell protoplasts, providing support for the hypothesis that MSL proteins form MS channels (5).…”
mentioning
confidence: 90%
“…MscS-like channels regulate volume and division of plastids in algae (Nakayama et al, 2007) and higher plants, including Arabidopsis (Haswell and Meyerowitz, 2006;Peyronnet et al, 2008;Wilson et al, 2011). Both MscL and MscS are found in the same bacterial cell and show functional redundancy, but in contrast with MscL, MscS is a heptamer with three TM domains (Bass et al, 2002).…”
Section: Mechanosensitive Channels In Bacteriamentioning
confidence: 99%
“…The abi4-1 allele was genotyped with oligos TCAAT-CCGATTCCACCACCGAC and CCACTTCCTCCTTGTTCCTGC, and digesting with NlaI. PCR genotyping of msl, p5cs1 and aba2-1 alleles was performed as previously described Szekely et al, 2008;Wilson et al, 2011).…”
Section: Arabidopsis Thaliana Mutantsmentioning
confidence: 99%
“…Quantitative reverse transcription-PCR was performed as previously described (Wilson et al, 2011). Primers used for gene expression analysis of ACTIN and ARR genes were previously described (Wilson et al, 2014;Zhao et al, 2010).…”
Section: Quantitative Reverse Transcription-pcrmentioning
confidence: 99%
See 1 more Smart Citation